2015
DOI: 10.1210/me.2015-1084
|View full text |Cite
|
Sign up to set email alerts
|

Ubc9 Impairs Activation of the Brown Fat Energy Metabolism Program in Human White Adipocytes

Abstract: Insulin resistance and type 2 diabetes mellitus (T2DM) result from an inability to efficiently store and catabolize surplus energy in adipose tissue. Subcutaneous adipocytes protect against insulin resistance and T2DM by coupling differentiation with the induction of brown fat gene programs for efficient energy metabolism. Mechanisms that disrupt these programs in adipocytes are currently poorly defined, but represent therapeutic targets for the treatment of T2DM. To gain insight into these mechanisms, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 71 publications
4
15
0
Order By: Relevance
“…5E). Together, our findings demonstrate that the depletion of Ubc9 stimulates PPAR␥ activity (13) and stabilizes PRDM16, corresponding to activation of the BAT energy metabolism program in human adipocytes.…”
Section: Manipulation Of Ubc9 Expression By Sirna or A Mir-30a Mimicsupporting
confidence: 56%
See 4 more Smart Citations
“…5E). Together, our findings demonstrate that the depletion of Ubc9 stimulates PPAR␥ activity (13) and stabilizes PRDM16, corresponding to activation of the BAT energy metabolism program in human adipocytes.…”
Section: Manipulation Of Ubc9 Expression By Sirna or A Mir-30a Mimicsupporting
confidence: 56%
“…Previous data established that PRMD16 and PPAR␥ interact to promote expression of thermogenic genes in subcutaneous adipocytes (11,24). These data, combined with our recent observation that Ubc9 interacts with PPAR␥ (13), suggested that Ubc9 may interact with PRDM16 as part of a complex. As shown in Fig.…”
Section: Manipulation Of Ubc9 Expression By Sirna or A Mir-30a Mimicmentioning
confidence: 54%
See 3 more Smart Citations